How does the impact of the COVID-19 pandemic on Indonesia's Islamic stock returns? - Agustin, Isnaini Nuzula (University of Islam Malang, 2021)
The unprecedented COVID-19 pandemic has ripped down the worldwide economies since the beginning of 2020. The stock market was one of the economic sectors that experienced depression and crashed during the pandemic. In this study, we mount an investigation on how Indonesia's large-scale social restrictions (known as